Antibacterial Activity Test of Olive Leaf (Olea europaea L.) Extract Eyes Ointment on The Growth of Staphylococcus aureus - Harun, Nurhidayati; Ramdhani, Susan Sintia; Hariandja, Ahfira Puteri (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The use of herbal medicines is rapidly increasing among people around the world. Olive (Olea europaea L.) is a plant that has many known benefits, one of which is as an antibacterial. However, there is still minimal research using olive leaf as an antibacterial. The purpose of this study was to determine the antibacterial activity of olive leaf extract eye ointment on Staphylococcus aureus. Three formulations of eye ointment with the active ingredient of olive leaf extract (Olea europaea L.), with concentrations of 25%, 50%, 75%. All eye ointment preparations are tested for physical properties, including organoleptic tests, homogeneity tests, pH tests, spreadability tests, adhesion tests and sterility tests. The antibacterial activity was tested using the well method technique by calculating the inhibition zone. The physical quality test results show that all formulas comply with good formula standards. Zone of inhibition (mm) antibacterial activity test showed that the concentrations of olive leaf extract eye ointment at 25% (15.67), 50% (16.67), and 75% (17.67 ). It can be concluded that the higher the concentration of the extract, the greater the inhibitory power given. Olive extract eye ointment is able to provide antibacterial effects, especially at a concentration of 75% which can inhibit the growth of Staphylococcus aureus